ANALISIS PENGGUNAAN FINANCIAL TECHNOLOGY (FINTECH) di KALANGAN MASYARAKAT (STUDI KASUS: KONSUMEN PLAYGROUND X DI KOTA CIREBON - Nurhajijah, Sitta; Fariza, Muthia; Gunawan, Jessica Febriana; Fazria Mustofa, Siti Nurhaliza (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
In the development of the era of globalization 5.0, Indonesia has changed rapidly, there are increasingly developing technological advances. Technological advances are able to create new things and develop new thoughts (Adiningsih, 2019). The rapid development of technology in society is able to change the mindset of society globally, both in positive and negative terms because the role of technology is very important in determining people's welfare and triggering acts that are against the law (Ramli, 2007). Based on research results, Financial Technology (Fintech) among the public has been well implemented. It can be concluded that Playground X uses a payment strategy through Financial Technology (Fintech) in running its business in order to attract consumers' interest and be able to build a positive image, as seen from consumers who have experienced payment through Financial Technology (Fintech). With technological advances and digitalization when making payments at Playground X, it provides excellent value to increase Playground X's business interests. By implementing Financial Technology (Fintech) in the community, it has a positive impact on Playground X because it is considered capable of providing services that are in line with what consumers expect.